2016
DOI: 10.24017/science.2016.1.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and morphometric study of Echinococcus granulosus (metacestode) in Sulaimani Province/ Kurdistan Region, Iraq

Abstract: Hydatid disease (echinococcosis) is a parasitic infection caused by the larval stage ofEchinococcus granulosus with the global distribution. This disease is endemic in Iraq and Kurdistan Region with no strategy and long-term control plan. The strain identification of this parasite is essential to improve both monitoring and prevention of the disease. For this reason, the present on the morphological characterization of the larval stage of Echinococcus granulosus isolated from sheep, cattle, and human beings, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The results of the current study are consistent with a study (Hama & Shareef, 2016) in Sulaymaniyah city, where it found that the average total length of the LH isolated from sheep was 22.24 ± 1.300 µm, and the BL measurement of the LH which are isolated from sheep was 10.55 ± 1.700 µm. This study also recorded that the total length of the SH was 0.900 ± 17.60 µm, and the BL of the SH measured 1.00 ± 8.10 µm.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study are consistent with a study (Hama & Shareef, 2016) in Sulaymaniyah city, where it found that the average total length of the LH isolated from sheep was 22.24 ± 1.300 µm, and the BL measurement of the LH which are isolated from sheep was 10.55 ± 1.700 µm. This study also recorded that the total length of the SH was 0.900 ± 17.60 µm, and the BL of the SH measured 1.00 ± 8.10 µm.…”
Section: Discussionsupporting
confidence: 92%
“…In general, in the case of neighbouring countries there was a low diversity in the animal hosts examined and subsequently in CE genotypes isolated, with most studies focused on E. granulosus s.s. (Utuk et al , 2008; Latif et al , 2010; Simsek et al , 2011; Eryıldız & Şakru, 2012; Hama et al , 2012; Hama & Shareef, 2016; Hasan et al , 2016; Gökpınar et al , 2017; Hassan et al , 2017). With some exceptions (Al-Qaoud et al , 2003; Trachsel et al , 2007; Ziadinov et al , 2008), the strains identified in definitive hosts in Iran are partly identical to detected genotypes in adjacent countries.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular-based methods are not alternative of inspection methods for cyst detection, while the combination between direct inspection and DNA markers are important to understanding the nature and origin of cysts [31] The morphological and biochemical markers are helpful for species and strain identification of Taenia spp. while the molecular and DNA markers are more accurate and dependable for molecular epidemiology study [32]. The DNA marker and molecular characterization are valuable for species and strain identification of Taenia species [33,34].…”
Section: Discussionmentioning
confidence: 99%